2020
DOI: 10.1097/gox.0000000000003226
|View full text |Cite
|
Sign up to set email alerts
|

Tip of the Tongue Reconstruction with Prelaminated Fasciomucosal Radial Forearm Free Flap

Abstract: Summary: Tongue cancer is the most common malignant neoplasm of the oral cavity. Occurrence in the tip of the tongue (TOT) is rare. We describe a case report of a TOT tumor excision and reconstruction with a prelaminated fasciomucosal radial forearm free flap. A 41-year-old white man was referred to our department for a squamous cell carcinoma of the tip of the tongue. The patient worked as an air traffic control official; therefore, conservation of speech intelligibility, both in Italian and Engli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…A total of 19 studies was included in this systematic review, as showed by the PRISMA flow diagram (Figure 1 ) (Alves et al, 2020 ; Chiarini et al, 2002 ; Collar & Byrne, 2013 ; Colletti et al, 2012 ; Jehn et al, 2019 ; Kilinc & Aytekin, 2014 ; Kim et al, 2013 ; Lauer et al, 2001 ; Maruccia et al, 2020 ; Nehrer‐Tairych et al, 2002 ; Poeschl et al, 2003 ; Rath et al, 1999 ; Sadigh & Jeng, 2015 ; Schlenz et al, 2001 ; Teng et al, 2005 ; Upton et al, 1994 ; Wolff et al, 1996 ; Ziegler & Oyer, 2021 ). Seven out of the selected 19 articles were case reports (Alves et al, 2020 ; Collar & Byrne, 2013 ; De Santis et al, 2020 ; Maruccia et al, 2020 ; Sadigh & Jeng, 2015 ; Teng et al, 2005 ; Ziegler & Oyer, 2021 ), while the remaining 12 articles were case series (with five out of them including less than five cases) (Chiarini et al, 2002 ; Colletti et al, 2012 ; Jehn et al, 2019 ; Kilinc & Aytekin, 2014 ; Kim et al, 2013 ; Lauer et al, 2001 ; Nehrer‐Tairych et al, 2002 ; Poeschl et al, 2003 ; Rath et al, 1999 ; Schlenz et al, 2001 ; Upton et al, 1994 ; Wolff et al, 1996 ). The whole study population was represented by 102 patients (63 males, 30 females, 9 not specified) undergoing reconstruction of an anatomical defect secondary to oncological ablative surgery with a prelaminated flap, over the last 27 years (1994–2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 19 studies was included in this systematic review, as showed by the PRISMA flow diagram (Figure 1 ) (Alves et al, 2020 ; Chiarini et al, 2002 ; Collar & Byrne, 2013 ; Colletti et al, 2012 ; Jehn et al, 2019 ; Kilinc & Aytekin, 2014 ; Kim et al, 2013 ; Lauer et al, 2001 ; Maruccia et al, 2020 ; Nehrer‐Tairych et al, 2002 ; Poeschl et al, 2003 ; Rath et al, 1999 ; Sadigh & Jeng, 2015 ; Schlenz et al, 2001 ; Teng et al, 2005 ; Upton et al, 1994 ; Wolff et al, 1996 ; Ziegler & Oyer, 2021 ). Seven out of the selected 19 articles were case reports (Alves et al, 2020 ; Collar & Byrne, 2013 ; De Santis et al, 2020 ; Maruccia et al, 2020 ; Sadigh & Jeng, 2015 ; Teng et al, 2005 ; Ziegler & Oyer, 2021 ), while the remaining 12 articles were case series (with five out of them including less than five cases) (Chiarini et al, 2002 ; Colletti et al, 2012 ; Jehn et al, 2019 ; Kilinc & Aytekin, 2014 ; Kim et al, 2013 ; Lauer et al, 2001 ; Nehrer‐Tairych et al, 2002 ; Poeschl et al, 2003 ; Rath et al, 1999 ; Schlenz et al, 2001 ; Upton et al, 1994 ; Wolff et al, 1996 ). The whole study population was represented by 102 patients (63 males, 30 females, 9 not specified) undergoing reconstruction of an anatomical defect secondary to oncological ablative surgery with a prelaminated flap, over the last 27 years (1994–2021).…”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, only 5.9% of patients from group C (reconstruction with prelaminated flap as a primary cancer treatment) encountered post‐operative complications. Only in two patients within group C data regarding adjuvant radiation therapy were reported, with a satisfactory morphological and functional results (Chiarini et al, 2002 ; De Santis et al, 2020 ). It was not possible to evaluate data regarding duration of hospitalization and long‐term complications, since data regarding surgical outcome achieved a mean follow‐up of 17 months (range 0.5–30.4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accurate physical examination and assessment of the lymphedema severity are essential to provide more predictable outcomes. A prompt management of the disease in a multidisciplinary team is the key to obtain good results [ 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 ]. Despite the fact lymphedema is still considered an incurable disease, in the last decade promising results with significant reduction of the limb swelling and improvement of psychosocial well-being have been shown.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the surgical background can significantly interfere with the surgeon's choices in traumatic emergencies as well as in elective procedures both in hand and plastic surgery [ 37 ]. Different surgical aspects have to be taken into considerations when facing with the patient: detailed knowledge of the topic and all surgical solutions [ 38 ]; technical possibilities according to hospital class (hub or spoke center) and epidemiologic challenges such as emerging COVID-19 pandemic [ [39] , [40] , [41] , [42] ]; required instruments to perform microsurgery [ [43] , [44] , [45] , [46] , [47] ]; use of new technologies, innovative surgical methods and unconventional devices [ [48] , [49] , [50] , [51] , [52] ]; possibility to refer to skilled consultants; possibility to work in multi-equip with different specialists [ [53] , [54] , [55] , [56] , [57] , [58] ]; selection of high-risk surgical wound complications patients throughout available scores [ 59 , 60 ]; the help of skilled health professionals able to early detect possible complications and promptly start proper care and close follow-up [ 61 , 62 ]. …”
Section: Discussionmentioning
confidence: 99%